Improved tribocorrosion behavior obtained by in-situ precipitation of Ti2C in Ti-Nb alloy - Gonçalves, Vinícius Richieri Manso (2022)
Novel in-situ Ti-based matrix composites (TMCs) were developed through the reactive hot pressing of Ti + NbC powder blends. Due to the chemical reaction that occurred in the solid-state during processing, the produced samples were composed of an Nb-rich β-Ti phase that formed a metallic matrix along with Ti2C as a reinforcing phase. By employing different proportions of Ti:NbC, the phase composition of the alloys was designed to contain different ratios of α-Ti and β-Ti. The present work investigated the corrosion and tribocorrosion behavior of the composites, compared to unreinforced Ti, in a phosphate-buffered solution (PBS) at body temperature. Corrosion tests included potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Tribocorrosion tests were carried out using a ball-on-plate tribometer with sliding performed at open circuit potential (OCP) and under anodic potentiostatic conditions. Results showed that the stabilization of the β phase in the matrix led to a decrease in the hardness. However, the formation of the in-situ reinforcing phase significantly improved the tribocorrosion behavior of the composites due to a load-carrying effect, lowering the corrosion tendency and kinetics under sliding. Furthermore, localized corrosion was not observed at the interface between the reinforcing phase and the matrix.